Munda Make Over Series 3: Climate smart agriculture - Gamoyo, Majambo Jarumani; Koech, Grace Jerotich; Chilambe, Pedro Anglaze; Ghosh, Aniruddha; Kasuba, Chileya (2025)
This Series 3 of Munda Makeover episodes brings climate information and sustainable farming practices to Zambian smallholder farmers through engaging, research-based content. The weather-focused episodes provide seasonal outlooks and climate information to help farmers make informed decisions about planting, crop selection, and farm management. Five episodes focus on regenerative agriculture practices that build soil health, enhance resilience, and promote sustainable production systems adapted to climate variability. An additional episode addresses agricultural mechanization techniques to improve farm productivity and efficiency. Broadcast in Nyanja, Bemba, and English on ZNBC TV 1, and disseminated through social media platforms like Youtube, these episodes ensure that critical climate and agricultural information reaches farmers across Zambia, supporting climate-smart decision-making and building resilience in farming communities.